2021
DOI: 10.3390/rel12100846
|View full text |Cite
|
Sign up to set email alerts
|

God’s Perceived Engagement/Disengagement in Response to Prayer and Interpersonal Forgiveness: The Mediating Role of Positive Orientation

Abstract: It is well documented that religion and its different aspects positively affect people’s ability to forgive. However, studies have rarely moved beyond direct associations to explore potential mediators of this relationship. In this context, our main aim was to examine the direct relationship between God’s engagement/disengagement in response to prayer and forgiveness with the possible influence of a positive orientation. Data were gathered from 464 participants aged 18 to 75 (M = 31.10; SD = 11.32). This study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…For the first goal, we used an index of tolerance less than 0.2 and variance inflation factors (VIFs) higher than 5.0 as indicatives of high intercorrelations ( Świ ątek et al 2021). For the second aim, we used the value of Mahalanobis' distance not being lower than p = 0.001 and the value of Cook's distance not being higher than 1 (Szcześniak and Strochalska 2021). To realize the third objective, we chose the variables of sex, age, and religious engagement.…”
Section: Discussionmentioning
confidence: 99%
“…For the first goal, we used an index of tolerance less than 0.2 and variance inflation factors (VIFs) higher than 5.0 as indicatives of high intercorrelations ( Świ ątek et al 2021). For the second aim, we used the value of Mahalanobis' distance not being lower than p = 0.001 and the value of Cook's distance not being higher than 1 (Szcześniak and Strochalska 2021). To realize the third objective, we chose the variables of sex, age, and religious engagement.…”
Section: Discussionmentioning
confidence: 99%
“…The value of the Chi-square still showed a poor fit (39.399, degrees of freedom = 19), presenting a statistically significant p = 0.003. However, the current sample was larger than that of Study 2, which often results in a significant p value (Szcześniak and Strochalska 2021). Inspection of local fit indices showed good standardized factor loadings that ranged from 0.78 to 0.96 (Figure 3).…”
Section: Resultsmentioning
confidence: 92%
“…Conversely, a perception of God as silent and disconnected from people (a marginal religious position) may induce less positivity, and therefore, impede forgiveness. (Szcześniak & Strochalska, 2021) Another study with 368 kids found a statistically significant connection between forgiveness and terminal values (the desired end-states that a person strongly wants to achieve such as "a comfortable life", "freedom", or "salvation.") and meaning in the lives of the participants.…”
Section: Forgiveness and Religionmentioning
confidence: 99%